2019
DOI: 10.1002/app.47967
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Bis(2,3‐dicarboxyl‐phenoxy)benzene dianhydride‐based phenylethynyl terminated thermoset oligoimides for resin transfer molding applications

Abstract: A series of thermoset oligoimides have been prepared by the thermal polycondensation of 1,4-bis(2,3-dicarboxyl-phenoxy)benzene dianhydride with three different aromatic diamines in the presence of 4-phenylethynylphthalic anhydride as an end capping reagent. The aromatic diamines included 4,4 0 -oxydianiline, 2,2 0 -bis(trifluoromethyl)benzidine (TFDB) and 2-phenyl-4,4 0 -diaminodiphenyl ether (p-ODA). Effects of the chemical structures and molecular weights of the oligoimides on their aggregated structures, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…4-Phenylethynyl phthalic anhydride (PEPA) is a kind of terminating agent for PI, and the terminal phenylethynyl group can cure PI by a chemical cross-linking reaction at high temperatures, 49 retaining the degree of order of PI molecular chains. 50 However, how to prepare LC-PI with a liquid crystal range containing the curing temperature and to achieve controlled curing within the liquid crystal range have become the key issues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4-Phenylethynyl phthalic anhydride (PEPA) is a kind of terminating agent for PI, and the terminal phenylethynyl group can cure PI by a chemical cross-linking reaction at high temperatures, 49 retaining the degree of order of PI molecular chains. 50 However, how to prepare LC-PI with a liquid crystal range containing the curing temperature and to achieve controlled curing within the liquid crystal range have become the key issues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Crosslinking additives thermally decompose at high temperatures to form free radicals, which react with the monomer molecular chain to form macromolecular chain radicals in the presence of the LDPE monomer to initiate the polymerization reaction. In the absence of a monomer, it will further decompose into primary radicals (where j represents various primary radicals) [ 27 , 28 , 29 ]. At the same time, the primary radicals will react with the surrounding polymer long chain, so that it loses free electrons to form long chain radicals due to the high activity of the primary radicals further reacting with other polymer long chains; the formation of the reaction chain continues to increase, polyethylene molecular chains crosslink with each other to ultimately form a three-dimensional mesh structure, and the high activity of free radicals is finally consumed in chain reaction termination [ 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Asymmetric diamine, 2-phenyl-4,4'-diaminophenyl ether (p-ODA), was also suitable for synthesizing PETIs with greater processablity. [19,32] Fang et al [33] reported RTMable PETIs featured low melting viscosities at low temperatures. The melting viscosities of the PETIs maintain below 1 Pa•s for 2 h in isothermal rheological tests in the temperature range of 220−280 °C.…”
Section: Introductionmentioning
confidence: 99%